Study guide to accompany Modern auditing - Coram, Paul.; Gill, Gurdarshan (Milton, Qld. : John Wiley and Sons, 1999)
Auditing and the public accounting profession. Financial report audits. Professional ethics and conduct. Auditor's legal liability. Audit objectives, evidence and working papers. Accepting the engagement and planning the audit. Materiality, risk and preliminary audit strategies...
Keywords: Economics; Auditing; Auditing -- Australia -- Problems, exercises, etc